Cerebral Proliferative Angiopathy as the Cause of Symptomatic Epilepsy in a Young Adult Male: A First Case Report from Indonesia - Jovian Philip Swatan; Achmad Firdaus Sani; Wardah Rahmatul Islamiyah; Dedy Kurniawan; Ersifa Fatimah (Magna Neurologica, 2024)
Background: Cerebral proliferative angiopathy (CPA) is a rare and distinct vascular malformation that was once considered a subset of cerebral arteriovenous malformation (AVM). Due to its relatively benign course with no distinctive clinical feature, CPA may often be overlooked and misdiagnosed with other diseases. We would like to report a case of CPA as the underlying cause of symptomatic epilepsy. Case: A 31-year-old male presented to the outpatient clinic with a history of focal to bilateral tonic-clonic seizure for 2 years. Following conservative management with an oral antiepileptic agent, the seizure frequency significantly decreased from once daily to once or twice monthly. The patient was lost to follow-up; however, he was incidentally referred back to our clinic two years later for further evaluation. A head Magnetic Resonance Imaging and Magnetic Resonance Angiography revealed a suspicion of giant AVM in the left hemisphere. Cerebral digital subtraction angiography (DSA) was performed and revealed a CPA in the left frontal area. The patient was managed conservatively, and during the 6-month follow-up period, the patient did not have any seizures. Discussion: In young adults, seizures may be caused by an underlying vascular abnormality. Cerebral DSA remained the gold standard for distinguishing various etiologies of vascular malformation, including CPA. Conclusion: Conservative treatment using oral antiepileptic agents was effective in controlling the seizure frequency in CPA. However, a complete diagnostic evaluation is still warranted to determine the most appropriate treatment while revealing some peculiar and unexpected etiologies in the process.